2015
DOI: 10.1681/asn.2015030301
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Coronary Flow Reserve in Patients with Dialysis-Dependent ESRD

Abstract: Capillary rarefaction of the coronary microcirculation is a consistent phenotype in patients with dialysisdependent ESRD (dd-ESRD) and may help explain their excess mortality. Global coronary flow reserve (CFR) assessed by positron emission tomography (PET) is a noninvasive, quantitative marker of myocardial perfusion and ischemia that integrates the hemodynamic effects of epicardial stenosis, diffuse atherosclerosis, and microvascular dysfunction. We tested whether global CFR provides risk stratification in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…108 Two series from one center have shown that PET measures of MFR have greater prognostic value than do clinical and relative MPI parameters in patients with chronic kidney disease 109 and patients requiring renal replacement therapy. 110 Cardiomyopathy and Heart Failure. In many cases, relative MPI lacks sufficient negative predictive value to adequately rule out an ischemic etiology in patients with severe reductions in systolic function.…”
Section: Treatment Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…108 Two series from one center have shown that PET measures of MFR have greater prognostic value than do clinical and relative MPI parameters in patients with chronic kidney disease 109 and patients requiring renal replacement therapy. 110 Cardiomyopathy and Heart Failure. In many cases, relative MPI lacks sufficient negative predictive value to adequately rule out an ischemic etiology in patients with severe reductions in systolic function.…”
Section: Treatment Guidancementioning
confidence: 99%
“…(Adapted from Naya et al 91 ). [159][160][161][162][163] and chronic kidney disease 109,110,164,165 ).…”
Section: Reporting Quantitative Mbf Datamentioning
confidence: 99%
“…Although the accuracy of dobutamine stress echocardiogram and SPECT in detecting obstructive CAD (≄70% stenosis) in renal transplantation candidates was not statistically different in a meta‐analysis,33 the presence of concentric and eccentric LVH, common in ESRD, may affect the accuracy of dobutamine stress echocardiogram 34. PET imaging assesses not only myocardial blood flow but also coronary flow reserve, which can provide additional insights into early stages of atherosclerosis and microvascular dysfunction 35, 36. Recently, coronary flow reserve assessed by cardiac PET has been shown to provide incremental risk stratification for cardiovascular and all‐cause mortality in patients on dialysis, even in the absence of overt cardiovascular disease 36.…”
Section: Cad In Patients With Esrdmentioning
confidence: 99%
“…PET imaging assesses not only myocardial blood flow but also coronary flow reserve, which can provide additional insights into early stages of atherosclerosis and microvascular dysfunction 35, 36. Recently, coronary flow reserve assessed by cardiac PET has been shown to provide incremental risk stratification for cardiovascular and all‐cause mortality in patients on dialysis, even in the absence of overt cardiovascular disease 36. For the highest risk patients, PET may be advantageous because it has superior sensitivity for detecting CAD 35, 36.…”
Section: Cad In Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation